Estimating cost adjustments required to accomplish target savings in chronic disease management interventions: a simulation study. (July 2015) - Diaz, Rafael; Behr, Joshua G; Britton, Bruce S
Chronic diseases are persistent ailments that are not preventable or curable with medication or vaccination. Many of the leading chronic conditions in industrialized societies may be related to lifestyle choices. The prevalence of these chronic conditions significantly affects the health, suffering, and longevity of patients. This paper demonstrates the utility of system dynamics as an approach to model and simulate the behavior of key cost factors in the implementation of population health management interventions. The study uses modeling and simulation as an evaluative method to identify potential savings stemming from an intervention within a well-defined population group. The model is flexible in that it allows policy-makers the ability to set saving targets that, in turn, generate knowledge about the cost structure adjustments necessary to reach these targets. The model provides useful insights into how the initial estimates of the cost of intervention, the resulting savings, and potential costs adjustments may change. The functionality of the model is demonstrated by means of scenarios implemented via sensitivity analysis.